Genomic Epidemiology of Antimalarial Drug Resistance in Plasmodium falciparum in Southern China - Huang, Fang; Jacob, Christopher G.; Takala-Harrison, Shannon; Adams, Matthew; Yang, Heng-Lin; Liu, Hui; Xia, Zhi-Gui; Zhou, Shui-Sen; Tang, Lin-Hua; Plowe, Christopher V. (Frontiers in Cellular and Infection Microbiology, 2021)
Emerging artemisinin resistance in Southeast Asia poses a significant risk to malaria control and eradication goals, including China’s plan to eliminate malaria nationwide by 2020. Plasmodium falciparum was endemic in China, especially in Southern China. Parasites from this region have shown decreased susceptibility to artemisinin and delayed parasite clearance after artemisinin treatment. Understanding the genetic basis of artemisinin resistance and identifying specific genetic loci associated with this phenotype is crucial for surveillance and containment of resistance. In this study, parasites were collected from clinical patients from Yunnan province and Hainan island. The parasites were genotyped using a P. falciparum-specific single nucleotide polymorphism (SNP) microarray. The SNP profiles examined included a total of 27 validated and candidate molecular markers of drug resistance. The structure of the parasite population was evaluated by principal component analysis by using the EIGENSOFT program, and ADMIXTURE was used to calculate maximum likelihood estimates for the substructure analysis. Parasites showed a high prevalence of resistance haplotypes of pfdhfr and pfdhps and moderate prevalence of pfcrt. There was no mutation identified on pfmdr1. Candidate SNPs on chromosomes 10, 13, and 14 that were associated with delayed parasite clearance showed a low prevalence of mutants. Parasites from Southern China were clustered and separated from those from Southeast Asia. Parasites from Yunnan province were substructured from parasites from Hainan island. This study provides evidence for a genomic population with drug resistance in Southern China and also illustrates the utility of SNP microarrays for large-scale parasite molecular epidemiology.